(untitled) (International Seven Journal of Health Research, 2024)
Bacterial endocarditis is a recurring pathology in health services around the world, and various etiological agents can be involved, which can modify the course of the disease according to the degree of infection and aggressiveness of the pathogen. However, a complex relationship is established when this condition is triggered by a specific bacterium, Streptococcus gallolyticus¸ popularly known as S. bovis, since observational studies have linked the presence of this Gram-positive coccus to colorectal carcinomas1.